Establishing and maintaining cell polarity with mRNA localization in Drosophila. (15th January 2016) - Barr, Justinn; Yakovlev, Konstantin V.; Shidlovskii, Yulii; Schedl, Paul
Abstract : How cell polarity is established and maintained is an important question in diverse biological contexts. Molecular mechanisms used to localize polarity proteins to distinct domains are likely context‐dependent and provide a feedback loop in order to maintain polarity. One such mechanism is the localized translation of mRNAs encoding polarity proteins, which will be the focus of this review and may play a more important role in the establishment and maintenance of polarity than is currently known. Localized translation of mRNAs encoding polarity proteins can be used to establish polarity in response to an external signal, and to maintain polarity by local production of polarity determinants. The importance of this mechanism is illustrated by recent findings, including orb2 ‐dependent localized translation of aPKC mRNA at the apical end of elongating spermatid tails in the Drosophila testis, and the apical localization of stardust A mRNA in Drosophila follicle and embryonic epithelia. Abstract : Asymmetric activation of translation is a mechanism for establishing polarity in response to an external signal. On‐site translation of an mRNA encoding a polarity determinant generates a high concentration of the polarity protein locally. Following establishment, mRNA localization and on‐site translation facilitates maintenance of polarity.